Language Games On Students To Upgrade Arabic Vocabulary Proficiency - Mishbahuddin, Mohamad; Hidayah, Zia Haninatul (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2021)
Among the various problems in learning Arabic at the school is the difficulty in creating an atmosphere of learning Arabic by teachers how to motivate students to learn Arabic. This condition is of course impact on learning Arabic held in class, especially when traced how the learning outcomes that will be generated. In connection with the problem, so in this paper put forward an alternative learning are expected to be more motivating to students in learning Arabic, which is through the use of various games in learning Arabic. With increasing student motivation to learn Arabic subjects, it is expected that ongoing learning will be more qualified. One reason for using of games in learning process is will adding to recreational game and also has a charge of education. With the game, someone will feel compelled to engage and overcome difficulties and solve problem. Keywords: Language, games, vocabulary.